1997
DOI: 10.1046/j.1471-4159.1997.69051829.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Differential Gene Induction of the Neuroendocrine‐Specific Genes Neurotensin, Neurotensin Receptor, PC1, PC2, and 7B2 in the Human Ocular Ciliary Epithelium

Abstract: Abstract:The ocular ciliary epithelium is a bilayer of neuroepithelial cells specialized in the secretion of aqueous humor fluid and the regulation of intraocular pressure. In this study, we report on the expression of the regulatory peptide neurotensin (NT) and a set of differentiated neuroendocrine markers including neurotensin receptors (NTrs), the prohormone convertasesfurin, PCi, and PC2, and the neuroendocrine polypeptide 7B2 in the ciliary epithelium. Using a human cell line, ODM-2, derived from the non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Some of these peptides, synthesized and released by the ciliary epithelium, are neuropeptides and hormones usually restricted to endocrine tissues and cells (Ortego et al, 1996a,b;Coca-Prados, 1997, 1999). Production and receptors for neurotensin (Ortego and Coca-Prados, 1997), galanin (Ortego and Coca-Prados, 1998), natriuretics peptides (Ortega and Coca-Prados, 1999;Fernandez-Durango et al, 1995), angiotensin II (Cullinane et al, 2002) and endothelins (Fernandez-Durango et al, 2003) have been identified in the pigmented and nonpigmented ciliary epithelium and in cells of the trabecular meshwork (Escribano and Coca-Prados, 2002). Having shown that ghrelin's mRNA is present in the posterior ephitelium of the iris and in the non-pigmented epithelium of the ciliary body the present study indicates that ghrelin possibly is also a product of that ''neuroendocrine gland''.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these peptides, synthesized and released by the ciliary epithelium, are neuropeptides and hormones usually restricted to endocrine tissues and cells (Ortego et al, 1996a,b;Coca-Prados, 1997, 1999). Production and receptors for neurotensin (Ortego and Coca-Prados, 1997), galanin (Ortego and Coca-Prados, 1998), natriuretics peptides (Ortega and Coca-Prados, 1999;Fernandez-Durango et al, 1995), angiotensin II (Cullinane et al, 2002) and endothelins (Fernandez-Durango et al, 2003) have been identified in the pigmented and nonpigmented ciliary epithelium and in cells of the trabecular meshwork (Escribano and Coca-Prados, 2002). Having shown that ghrelin's mRNA is present in the posterior ephitelium of the iris and in the non-pigmented epithelium of the ciliary body the present study indicates that ghrelin possibly is also a product of that ''neuroendocrine gland''.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of starting RNA was less than usual to avoid the melanin-associated inhibition of in vitro cDNA formation obtained with RNA extracted from the ciliary body [36]. The high PCR cycle number was chosen both to compensate for reduced input RNA, and to maximize sensitivity of detection.…”
Section: Reverse Transcriptase-phosphorylase Chain Reaction (Rt-pcr)mentioning
confidence: 99%
“…Many of the neuroendocrine peptides and hormones synthesized by the NPE cells are released and found in the aqueous humor with their neuropeptide-processing enzymes (5). Among the regulatory peptides identified figured neurotensin and natriuretic peptides, and the precursor of angiotensin, angiotensinogen, which are all known to modulate blood pressure in the cardiovascular system (7).…”
mentioning
confidence: 99%